Improving Inpatient Colonoscopy Preparation in a University Hospital: An Evidence-Based Practice Project. (March 2016) - Chambers, Karen; Whiteman, Kimberly; Stephens, Kimberly; Goodloe, Lauren; Kirsteen, Hal
Abstract : The majority of inpatient colonoscopy preparations at Virginia Commonwealth University Medical Center were rated as suboptimal, leading to incomplete or aborted procedures. These procedures needed to be rescheduled and delayed the patient's discharge from the hospital. An evidence-based practice model was used to implement an electronic colonoscopy order set. This resulted in improved quality of colon preparation and reduced canceled procedures. The potential savings for the hospital attributed to improvements in the bowel preparation processes for inpatient colonoscopies were calculated to be $418, 200.00 annually.